Early-Life Exposure to Lead Induces Cognitive Impairment in Elder Mice Targeting SIRT1 Phosphorylation and Oxidative Alterations - Zhang, Lijie; Tu, Runqi; Wang, Yawei; Hu, Yazhen; Li, Xing; Cheng, Xuemin; Yin, Yanyan; Li, Wenjie; Huang, Hui (Frontiers in Physiology, 2017)
Pb is a potential risk factor for cognition, mainly mediated by enhanced oxidative stress. Resveratrol, a natural polyphenol with crucial anti-oxidative property, is recently implicated in preventing cognitive deficits in normal aging and neurodegenerative disorders. Its beneficial effects have been linked to sirtuin 1(SIRT1) activation. The aim of this work is to investigate the possible linkage between alterations in Pb-induced oxidative damage and cognitive impairment by prolonged treatment of resveratrol. Male C57BL/6 mice were given Pb(Ac)2 treatment or deionized H2O for 12 weeks, and subjected to resveratrol gavage at the dose of 50mg/kgBw•d or vehicle after Pb exposure. Results from biochemical analysis and immunohistochemistry showed that Pb induced oxidative DNA damage and decreased cortical antioxidant biomarker. As expected, these abnormalities were improved by resveratrol treatment. Morris water maze test, Western blotting, immunofluorescence staining and RT-qPCR indicated that resveratrol ameliorated spatial learning and memory deficits with alterations in hippocampal BDNF-TrkB signaling, promoted nuclear localization and phosphorylation of hippocampal SIRT1, partly increased protein levels of AMPK and PGC-1α involving in modulation of antioxidant response in Pb-exposed mice. Our results support the hypothesis that resveratrol could attenuate Pb-induced cognitive impairment which was associated with activating SIRT1 via modulation of oxidative stress. Additionally, resveratrol also repressed the Pb-induce amyloidogenic processing with resultant decline in cortical Aβ1-40. Noteworthy, such effects were not mediated by resveratrol treatment alone. These findings emphasize the potential of SIRT1 activator as an efficacious dietary intervention to downgrade the Pb-induced neurotoxic lesion.